PMR Learning Model as Materials of Summary of 1st Grade Students - Fadlilah Salsabila Riyadi; Achmad Fathoni (Universitas Pendidikan Ganesha, 2022)
Mathematics education must begin when children enter school, namely at the elementary school level. The success of a student's education can be influenced by the learning approach used by the teacher. In particular, the additional lessons covered in the first grade of elementary school are very suitable for the PMR learning model. Learning to count can be facilitated by using candy-themed media and educational videos. The purpose of this study was to analyses the results of applying the PMR learning model to the educational process in relation to student learning. PTK which includes cycles I and II is the methodology of choice for this study. The PMR learning model was not implemented in Cycle I until after the pre-test was carried out. In Cycle II, we practiced the PMR learning paradigm with the help of learning videos and candy media. Twenty students from grade one at elementary school participated in this study. Data collection techniques were collected by tests and documentation. The result of this study show the average student score in cycle I was below the KKM standard. The KKM requirements were met with an average student in cycle II after the PMR learning model was applied. The findings from this study indicate that when the PMR learning paradigm is used together with learning videos and candy media, student learning outcomes show a significant increase.